2022
DOI: 10.1186/s12876-022-02438-z
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal anti-inflammatory drug exposure and the risk of microscopic colitis

Abstract: Background Medication consumption has been suggested as a risk factor for microscopic colitis (MC), but studies of varying design have yielded inconsistent results. Our aim was to evaluate the association between medications and MC. Methods A hybrid cohort of prospectively identified patients undergoing colonoscopy with biopsies for suspicion of MC (N = 144) and patients with MC enrolled within three months of diagnosis into an MC registry (N = 59)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In a separate secondary analysis, we also assessed whether the association of T1D with MC may be influenced by consumption of four medications: proton pump inhibitors (PPI, per Anatomical Therapeutic Chemical [ATC] code “A02BC01‐07”), selective serotonin reuptake inhibitors (SSRI, per ATC code “N06AB”), statin (per ATC code “C10”), and non‐steroidal anti‐inflammatory drugs (NSAIDs, per ATC codes “B01AC06”, “B01AC30” and “M01A”). Selection of medications was based on the reported associations with MC onset 18–21 . In order to be considered as MC‐associated, only medications dispensed within 180 days before biopsy were included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a separate secondary analysis, we also assessed whether the association of T1D with MC may be influenced by consumption of four medications: proton pump inhibitors (PPI, per Anatomical Therapeutic Chemical [ATC] code “A02BC01‐07”), selective serotonin reuptake inhibitors (SSRI, per ATC code “N06AB”), statin (per ATC code “C10”), and non‐steroidal anti‐inflammatory drugs (NSAIDs, per ATC codes “B01AC06”, “B01AC30” and “M01A”). Selection of medications was based on the reported associations with MC onset 18–21 . In order to be considered as MC‐associated, only medications dispensed within 180 days before biopsy were included.…”
Section: Methodsmentioning
confidence: 99%
“…Selection of medications was based on the reported associations with MC onset. [18][19][20][21] In order to be considered as MC-associated, only medications dispensed within 180 days before biopsy were included.…”
Section: Adjustment Of Covariatesmentioning
confidence: 99%
“…In studies that have found an association between MC and the use of PPIs and/or statins, the control group has mainly consisted of subjects from the general population; such associations have not been confirmed in control groups that consisted of patients with other causes of chronic diarrhea or in subjects referred for colonoscopy. 8 , 14 The rationale for PPIs and statins as a risk factor for MC are weakly based on current knowledge. First, both PPI 15 and statins 16 have shown anti-inflammatory effects on the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a separate study that utilized a combination of patients enrolled in a microscopic colitis registry and a prospective cohort of patients, only NSAIDs was linked to microscopic colitis. PPIs, H2Ras, SSRIs, statins, ACE-Is, and angiotensin receptor blockers (ARBs) were not linked to medication-induced microscopic colitis [16]. The strongest evidence for medication-induced microscopic colitis exist for only NSAIDs and Aspirin [16].…”
Section: Risk Factorsmentioning
confidence: 99%
“…PPIs, H2Ras, SSRIs, statins, ACE-Is, and angiotensin receptor blockers (ARBs) were not linked to medication-induced microscopic colitis [16]. The strongest evidence for medication-induced microscopic colitis exist for only NSAIDs and Aspirin [16]. The precise mechanism by which NSAIDs and Aspirin cause microscopic colitis has not been fully described.…”
Section: Risk Factorsmentioning
confidence: 99%